Liquid-like sorption water in the upper Martian surface - physical, chemical and possible biological consequences - Möhlmann, D.T.F. (European Space Agency, 2004)
Sorption water is a constitutent of the soul of the upper meters of the Martian surface at mid- and low latitudes (Möhlmann, 2004). This water content can regionally reach values of about 16 wt% (Feldman et al., 2003, Mitrofanov et al., 2003). Adsorption water, the physisorbed part of sorption water, can exist in a liquid-like state at temperatures down to -40° C and less. The terrestrial counterpart is the "unfrozen water" in permafrost (Anderson and Tice, 1972). It has partially modified physical, chemical and biological properties if compared to dry frozen soil. Liquid-like water can act as a solvent, and it supports transport processes to become effective. Chemical processes, which are triggered by adsorption water, are shown to be effective unter Martian conditions. These processes are energetically driven bye photons. Possibilities for a related photon driven bio-chemical Martian iron-carbon cycle are discussed.